A taxonomic review of the genus Ashibusa Matsumura, 1931 (Lepidoptera: Cosmopterigidae) from China - Zhang, Di; Li, Houhun (Zootaxa, 2023)
The genus Ashibusa Matsumura, 1931 is reviewed from China. Eight new species are described: A. apicodonta Li, sp. nov., A. biniprocessa Li, sp. nov., A. dilatirotunda Li, sp. nov., A. improjecta Li, sp. nov., A. ledongensis Li, sp. nov., A. longispina Li, sp. nov., A. similativalvula Li, sp. nov. and A. subfalcativalva Li, sp. nov. The females of A. flavalba Zhang & Li, 2009 and A. lativalvula Zhang & Li, 2009 are described for the first time. Images of adults and genitalia are provided for the new species and for the newly described female genitalia. A key to all the species and a map showing the distribution of these species are provided.